ANALYSIS OF CLINIC PROFILE OF PATIENTS WHO DID PHYSIOTHERAPY ADMITTED AT HOSPITAL SÃO LUCAS. (Fiep Bulletin - online, 2011)
The high complexity and responsibility demonstrated in the current scenario of Physiotherapy Hospital, the highly competitive market that includes due to fierce competition to provide service and planning ahead to prevent risks and with poor results, the differential intends to maintain and grow the market, and to that end, with physical therapy, the intention to improve the quality of life of patients who need it, with a special service and qualified, we sought to profile the population that demand in order to achieve success in the claim of the study. Delineate the clinical profile of patients admitted to St. Luke's Hospital who underwent physiotherapy. Through exploratory survey was conducted of data through the physical therapy evaluation forms of Cardiology and Pulmonology - Hospital in the period from April to June 2010, identifying gender, age and pathology, which were then tabulated, analyzed, interpreted and the result presented . 54% of the amount treated were female and 46% male. Regarding the age group 10% were between 11 and 20 years, 4% from 21 to 30 years, 10% of 31 to 40 years, 8% from 41 to 50 years, 13% from 51 to 60, 13 % from 61 to 70 years and 41% aged over 70 years. The pathologies found stand out stroke 40%, 28% for Postoperative trauma, 15% hypertension, 14% and 3% of CHF patients hospitalized for pneumonia. What we can observe is that the majority of patients, which represent 54% are female and 54% are aged over 61 years. The higher incidence of diseases and stroke are the Postoperative trauma, and the two together account for 68%.
Keywords: Hospital Physical Therapy; Clinical Profile; Epidemiology